A model of energy budgets over water, snow, and ice surfaces. Issue 10 (30th May 2014) - Wang, Jingfeng; Bras, Rafael L.; Nieves, Veronica; Deng, Yi
Abstract The recently formulated maximum entropy production (MEP) model over land surfaces has been generalized to water‐snow‐ice surfaces. Analytical solutions of energy budget in terms of the partition of surface radiative fluxes into (turbulent and/or conductive) heat fluxes at the earth‐atmosphere interface are derived as functions of surface temperature (e.g., sea surface temperature). The MEP model does not require data of wind speed, air temperature‐humidity, and surface roughness. Test of the MEP model using observations from several field experiments is encouraging. Potential applications of the proposed model for understanding long‐term trends in surface heat fluxes and for closing global surface energy budget at the Earth's atmosphere are suggested.